The German version of the brief affective neuroscience personality scales including a LUST scale (BANPS–GL) - Fuchshuber, Jürgen; Prandstätter, Theresa; Andres, Deborah; Roithmeier, Lisa; Schmautz, Beate; Freund, Anton; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Human Neuroscience, 2023)
Personality Scales (BANPS), which includes an additional subscale for the dimension LUST. The BANPS represents a shortened version of the Affective Neuroscience Personality Scales (ANPS), a self-report instrument to assess individual dispositions towards primary emotional systems as proposed by Jaak Panksepp.In a large sample (N = 926), the reliability and various facets of validity of the German translation of the BANPS were examined together with the newly included LUST scale. The BANPS-GL was related to the Big Five Inventory (BFI) and Sexual Sensation Seeking Scale (SSSS) and analyzed via confirmatory factor analysis (CFA).Results: Overall, the BANPS-GL exhibited reliabilities ranging from McDonald's ω = .70 (CARE) to α = .86 (SADNESS) and plausible correlations with external criteria. For CFA a correlated 7-factor model demonstrated good fit (TLI = .95; RMSEA = .04 (90% CI: 0.04, 0.05); SRMR = .06). A similar fit was demonstrated for a 2-higher-factor model (TLI = .93; RMSEA = .05 (90% CI: 0.05, 0.06); SRMR = .07).In broad agreement with the results of the original English version, the BANPS-GL showed good reliability and acceptable factorial validity, and overall improved the psychometric properties of the original long form. Finally, the inclusion of the dimension LUST allows for a complete coverage of the primary emotion dispositions as originally conceptualized by Panksepp.